Expectations and Experiences of Inbound Students: Perspectives from Sweden - Nilsson, Per A (Journal of International Students, 2015)
This paper explores expectations and outcomes for inbound students at Umeå University, Sweden, comparing their expectations with what they actually experienced. Based on an initial sample of 296 students, 116 answered surveys before and after experiencing of studying abroad. The same individuals have been followed. Most of the respondents’ expectations were fulfilled. Hence, the comprehension of what to expect when it comes to ‘personal’ experiences was shown to be in line with the respondents’ expectations. However, the ‘academic’ experiences seemed to be more difficult to grasp in advance. Some respondents also changed their opinions regarding some of their expectations. The study has followed the same individuals over time and adds new knowledge to the field of student mobility.